2017
DOI: 10.1186/s12862-016-0867-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic exaptation enables Lasius niger adaptation to urban environments

Abstract: BackgroundThe world is rapidly urbanizing, and only a subset of species are able to succeed in stressful city environments. Efficient genome-enabled stress response appears to be a likely prerequisite for urban adaptation. Despite the important role ants play in the ecosytem, only the genomes of ~13 have been sequenced so far. Here, we present the draft genome assembly of the black garden ant Lasius niger – the most successful urban inhabitant of all ants – and we compare it with the genomes of other ant speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Annotation of these sequences using blastx revealed that one of these genes is a Cytochrome P450 (CYP) reductase. Expansion of CYPs and sequence evolution in this family has been suggested to be linked with the success of L. niger in urban environments (Konorov et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Annotation of these sequences using blastx revealed that one of these genes is a Cytochrome P450 (CYP) reductase. Expansion of CYPs and sequence evolution in this family has been suggested to be linked with the success of L. niger in urban environments (Konorov et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…We aligned and quantified the raw reads using the RSEM 64 pipeline with Bowtie2 65 to transcripts from published genomes for A. mellifera , B. terrestris and L. niger 6668 . The L. niger genome assembly had no isoform information, so we identified isoforms using Tophat 69 .…”
Section: Methodsmentioning
confidence: 99%
“…Contigs annotated with known micro-organisms, and probable parasites such as viruses and fungi, were first filtered out from the data as exogenous material, as described in Johansson et al (2013) , and this exogenous material has now been made available in NCBI database (Bioproject: PRJNA412141 ). The remaining contigs were then aligned (BLASTx, e -value threshold 10 −3 ) to (a) the predicted gene sets of published ant genomes available on the Fourmidable database, including the closest species such as Camponotus floridanus , Lasius niger, as well as more distantly related species such as Cerapachys biroi , Linepithema humile , Solenopsis invicta , Vollenhovia emeryi , Wasmannia auropunctata , Pogonomyrmex barbatus , Monomorium pharaonis , Harpegnathos saltator , Acromyrmex echinatior and Atta cephalotes ( Wurm et al, 2011 ; Wurm et al, 2009 ; Bonasio et al, 2010 ; Suen et al, 2011 ; Smith et al, 2011a ; Smith et al, 2011b ; Nygaard et al, 2011 ; Gadau et al, 2012 ; Oxley et al, 2014 ; Schrader et al, 2014 ; Konorov et al, 2017 ), (b) the honey bee genome ( Weinstock et al, 2006 ), (c) the predicted gene sets of Nasonia vitripennis , Tribolium castaneum ( Wurm et al, 2009 ), and Drosophila melanogaster ( Gramates et al, 2017 ), (d) as well as non-redundant (NR) protein datasets available in the NCBI database (Updated 2015, Updated 2017) for insect species. A minimum requirement of 70% amino acid identity, and at least 100 bases (33 amino acids) alignment length was used.…”
Section: Methodsmentioning
confidence: 99%
“…Current genomic resources of social insects are available for important pollinators such as honey bees and bumble bees ( Colgan et al, 2011 ; Kocher et al, 2013 ; Elsik et al, 2014 ; Elsik et al, 2016 ; Kapheim et al, 2015 ; Sadd et al, 2015 ), and primitively eusocial paper wasps ( Sumner, Pereboom & Jordan, 2006 ; Ferreira et al, 2013 ). For ants, genome sequences are currently available for 13, and transcriptomes for 23, species in the Fourmidable database ( Wurm et al, 2009 ), including well studied species such as the invasive argentine ant (Linepithema humile) , the fire ant (Solenopsis invicta), and the leaf cutting ant species (Acromyrmex echinatior and Atta cephalotes ( Bonasio et al, 2010 ; Suen et al, 2011 ; Smith et al, 2011a ; Smith et al, 2011b ; Wurm et al, 2011 ; Nygaard et al, 2011 ; Gadau et al, 2012 ; Oxley et al, 2014 ; Schrader et al, 2014 ; Konorov et al, 2017 ). However, these data cover only a fraction of the genetic richness of the more than 11,000 described ant species, and over 100 million years of evolution ( Wilson & Hölldobler, 2005 ).…”
Section: Introductionmentioning
confidence: 99%